Arterio-Venous Malformation in the External Ear in Pregnancy - Normita S. Pangan (Philippine Journal of Otolaryngology Head and Neck Surgery, 2011)
Arterio-Venous Malformations (AVMs) are congenital vascular defects1 and are most commonly located in the head and neck area (81%).2 The majority of these were localized over the cheek (31%) , ear(16%), nose (10%),  forehead(10%), upper lip (7%),mandible (5%),neck (5%), and scalp and maxilla (4%). 2 There is equal predominance in males and females, and no racial predilection. 2  In general, there is “sparse literature about AVM in the external ear,”3 let alone its occurrence in a pregnant patient.